2008
DOI: 10.1097/nmd.0b013e31815faa5f
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Well-Being, Intrinsic Religiosity, and Suicidal Behavior in Predominantly Catholic Croatian War Veterans With Chronic Posttraumatic Stress Disorder

Abstract: We investigated relationships between spiritual well-being (SWB), intrinsic religiosity (IR), and suicidal behavior in 45 Croatian war veterans with chronic posttraumatic stress disorder and 32 healthy volunteers. Compared with the volunteers, the veterans had significantly lower SWB scores (p = 0.000) and existential well-being (EWB) scores (p = 0.000). Scores on the religious well-being (RWB) subscale (p = 0.108) and the IR scale did not differ significantly between the groups (p = 0.803). Veterans' suicidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…Suicide rates are usually not calculated and compared to the general population; however, some research has been performed on Russian veterans ( i.e. , Afghanistan and Chechnya), British Falkland conflict veterans, and Croatian local war veterans [39,40]. Deahl and co-authors [6] suggest that mental health problems of ex-military are diverse, polymorphic and have psychosocial consequences like social exclusion, homelessness, self-harm and substance abuse.…”
Section: Resultsmentioning
confidence: 99%
“…Suicide rates are usually not calculated and compared to the general population; however, some research has been performed on Russian veterans ( i.e. , Afghanistan and Chechnya), British Falkland conflict veterans, and Croatian local war veterans [39,40]. Deahl and co-authors [6] suggest that mental health problems of ex-military are diverse, polymorphic and have psychosocial consequences like social exclusion, homelessness, self-harm and substance abuse.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with what was expected, as the literature describes that African American women efficiently utilize protective factors of empowerment and resilience, such as spiritual means to cope with stress and reduce psychological symptoms (Taylor et al, 2004). Further, research with other populations has supported the links between both religious and existential well-being and PTSD symptoms (Lee & Waters, 2003; Nad et al, 2008). While existential and religious well-being both correlated with PTSD symptoms in the mediational model, existential well-being had a stronger association.…”
Section: Discussionmentioning
confidence: 97%
“…Studies with different populations have found that childhood maltreatment serves as a risk factor for lower levels of existential well-being, whereas one form of childhood maltreatment, childhood sexual abuse, has been linked to lower levels of religious well-being (Feinauer, Middleton, & Hilton, 2003; Weber & Cummings, 2003). Further, a negative association has been revealed between spiritual well-being, particularly existential well-being, and levels PTSD symptoms (Nad, Marcinko, Vuksan-Æusa, Jakovljevic, & Jakovljevic, 2008). However, a paucity of research examines these connections among African Americans.…”
mentioning
confidence: 99%
“…In particular, we included demographic factors, such as age, ethnicity (0 = Caucasian , 1 = ethnic or racial minority ), gender (0 = male , 1 = female ), and years of education in the statistical analyses. We also included assessments of previously examined predictors of suicide risk among veterans, including presence or absence of a strong religious faith (Nađ et al., ; Nelson, ) and presence or absence of a combat‐related injury (Bullman & Kang, ).…”
Section: Methodsmentioning
confidence: 99%
“…Most of these studies have focused on vulnerabilities, such as having elevated PTSD and depressive symptoms (Guerra & Calhoun, ; Jakupcak et al., ; Krysinska & Lester, ; Pietrzak et al., ), experiencing severe combat stressors and sustaining combat‐related injuries (Bullman & Kang, ), and being male and/or Caucasian (Kaplan et al., ; Zivin et al., ). Other studies have also focused on protective factors, such as psychological resiliency (Pietrzak et al., ), social support (Lemaire & Graham, ), as well as religiousness and existential well‐being (Nađ, Marčinko, Vuksan‐Æusa, Jakovljević & Jakovljevic, ; Nelson, ).…”
mentioning
confidence: 99%